180k views
3 votes
4(1-2) + 2(x + 3) = 6​

User SunSparc
by
4.3k points

2 Answers

3 votes

Answer:

2 = x

Explanation:

4(1 - 2) + 2(x + 3) = 6

4(-1) + 2x + 6 = 6

-4 + 2x + 6 = 6

2 + 2x = 6 [Combine like-terms]

-2 - 2

__________

2x = 4

___ __

2 2

x = 2

I am joyous to assist you anytime.

User Abhas
by
4.6k points
7 votes

4(1-2) + 2(x + 3) = 6

mutiply the first bracket by 4

(4)(1)= 4

(4)(-2)= -8

mutiply the second bracket by 2

(2)(x)= 2x

(2)(3)= 6

4-8+2x+6= 6

4-8+6+2x= 6

-4+6+2x= 6

2+2x= 6

move 2 to the other side

sign changes from 2 to -2

2-2+2x= 6-2

2x=6-2

2x= 4

divide by 2 for both sides

2x/2= 4/2

Answer: x= 2

User JakeofSpades
by
4.7k points